Pembentukan Produk Hukum Daerah dalam Rangka Penyelenggaraan Pemerintahan - Kurniawan Kurniawan (Universitas Syiah Kuala, 2013)
ABSTRACT: This is a legal empirical research by using the statutory approach. The study is a descriptive analysis. Primary and secondary data are applied and then analyzed qualitatively. The research shows that the Government of Aceh Tengah in the period between 2007 and 2012 has issued the number of local regulations in particular such as Qanun as much as 61 Qanun. From that total number are still againsts the applicable legislations, both from the substance and procedural aspects. In addition, the government has issued 221 of the District Head’s Decrees and 3139 it’s Decision. The Creation of Regional Law in a Part of Governance Conduct